PENGARUH PROFITABILITAS, LEVERAGE DAN OPINI AUDIT TERHADAP AUDIT DELAY - Wariyanti, Wariyanti; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe financial statements are the source of informations or communications about the financial and the operating activities of the company within a specific period that is used to describe the performance of the company.The time difference between the date of the financial statementand the date of the audit opinion on the financial statement indicatesthat the length of time in the audit completionwhich has been done by the auditor.This time difference in the audit is commonly called as audit delay. This researchis aimed to examine the influence of profitability, leverage, and the audit opinion to the audit delay. The population is all manufacturing companies which arelisted in Indonesia Stock Exchange (IDX) in 2012-2015 periods.The sample collection technique has been done by using specific criteria (purposive sampling) which have been desired by the researcher. The number of the samples in one year is as many as 44 companies, so 176 research objects within 4 years have been selected as samples. The data is the secondary data in the form of financial statements and company audit reports which has been obtained from Indonesia Stock Exchange (IDX). It has been found from the results of the research that profitability (ROA) does not giveany significant influenceto the audit delay whereas leverage (DER) and audit opinion give significant influence to the audit delay.Keywords: financial statements, audit reports, audit delay, profitability, leverage, audit opinion.